Influence of Regulating Pool on Bend Flow - LUO Fengjie; WU Yufeng; WEN Yunping; WANG Xumin; LI Xin (Renmin Zhujiang)
In view of the influence of regulating pool on the bend flow, based on experimental research, and combined with mathematical statistics and numerical simulation methods, this paper studies the influence of regulating pool on the hydraulic characteristics such as flow pattern and super-elevation by introducing the evaluation index of flow pattern improvement effect and analyzing typical working conditions. The results show that the regulating pool plays a role in dispersing the water surface super-elevation and improving the flow pattern, and the length of the regulating pool is an important parameter affecting the flow pattern improvement effect, with remarkable improvement effect in a certain range, but without effect beyond this range. There is a big error in the calculation result of the formula of water surface super-elevation with regulating pool, which needs to be corrected in practical engineering application.